Investigations into the design and fabrication of silicon photonic broadband wavelength selective switches and filters - Prabhathan, Patinharekandy (2012)
Silicon photonics offers great promise for widespread deployment of Opto Electronic Integrated Circuits (OEIC) and Photonic Integrated Circuits (PIC) devices in the near future. It is highly significant that silicon photonics allows Complementary Metal-Oxide-Semiconductor (CMOS) compatible fabrication of highly compact and efficient devices, in a cost effective way. Optical fiber communication network which uses Wavelength Division Multiplexing (WDM) technology needs highly efficient and sophisticated wavelength filtering functionality to meet the total bandwidth efficiency. Micro photonic technologies based on silicon waveguides are very promising in their functionality to provide telecom grade devices which meet these requirements. They are expected to escape the limitations of currently used bulk optical technologies in terms cost effective fabrication and implementation, stability, reconfigurability, compactness,complex wavelength routing/switching functionalities and integration with other active or passive devices. In this thesis investigations into the design and fabrication of Thermo Optic Wavelength Selective Switch (TO-WSS) and band pass filters in silicon platform is done to achieve desired spectral features and wavelength selection routing functionalities.